Examining the Role of Dietary Advanced Gycation End Products in Prostate Cancer Using Molecular Imaging Techniques (OR04-08-19). (13th June 2019) - Konopka, Christian; Paton, Annaliese; Skokowska, Aleksandra; Rowles, Joe; Erdman, John; Dobrucka, Iwona; Dobrucki, Lawrence
Abstract: Objectives: The Receptor for Advanced Glycation End Products (RAGE) and its ligands have been shown to be both over expressed and critical to prostate cancer (PCa) development. Importantly, the overexpression of both RAGE and its ligands is associated with poor PCa patient survival, suggesting its promise as a molecular target. Additionally, one of the largest sources of ligands for RAGE, advanced glycation end products (AGEs), come from one's diet and their concentrations are directly related to disease. We hypothesized that dietary AGEs (dAGEs) significantly contribute to the progression of PCa through interactions with RAGE. In this study we explore the use of a novel imaging strategy targeted at RAGE in combination with conventional imaging and histological techniques to assess the role of dAGEs on RAGE expression and PCa progression in murine xenografts. Methods: To examine the impact of AGEs on PCa cell function, experiments were performed in two PCa cell lines. Cells were grown in growth media enriched with carboxymethyl-lysine-modified human serum albumin (CML) (the most common AGE) or a control protein, bovine serum albumin (BSA). Western blot, confocal microscopy, clonogenic assays, and proliferations assays were performed. To study the effects of an enhanced consumption of dAGEs on PCa growth and progression in vivo, NU/J mice were fed a modified Ain-93 G diet, which was either CML or BSA enriched. PCa tumors were then initiated. Their growth was monitored, their perfusion measured using Speckle Contrast Imaging, and their metabolic rate and RAGE content quantified using 18FDG and a novel RAGE-targeted tracer using PET-CT. Finally, the tissues were excised for histological analysis. Results: CML significantly enhanced in vitro expression of both RAGE and proliferation marker KI-67. Cell doubling time was also significantly quickened, (1.5 vs 2.4 days) in the CML vs control. In vivo data demonstrated significant differences in tumor growth (CML group up to 2-fold increase) and successful tumor implantation rate (30% vs 60%). Perfusion, metabolism, and RAGE imaging demonstrated unique patterns which varied over the course of PCa progression. Conclusions: These studies indicate that dAGEs may play a significant role in the progression of PCa. The data suggests that RAGE and its ligands are promising targets for further therapeutic investigations. Funding Sources: University of Illinois at Chicago Cancer Center Pilot Grant. Supporting Tables, Images and/or Graphs: